Dr. Chembea Suleiman Athuman and Dr. Franz Kogelmann on female Islamic poetry in Zanzibar - Chembea, Suleiman; Kogelmann, Franz (Cluster Conversations, 2024)
In this episode of the Cluster Conversations Dr. Franz Kogelmann talks with Cluster fellow Dr. Chembea Suleiman Athuman about his project "Poetry (Qasidah) and Women’s Bodies in the Creation, Dissemination of Islamic Knowledge and Cultural Identity in Zanzibar". The study examines how active involvement of women in Islamic poetry (qasidah) helps (de-)construct traditional dynamics in the production and dissemination of Islamic knowledge and creation of cultural identity(-ies) along the East African coast. While Islamic knowledge production and dissemination was largely associated with male ulama (clerical class) in textual and religious spaces, advancement of media technology has caused a shift where qasidah not only support religious themes but also provide variations in the creation and transmission of knowledge and religious community identity. This shift, though rapidly gaining currency across Muslim communities, is explored within the microcosm of Zanzibar to understand how performance of poetry presents an avenue through which Muslim women engage with religious discourses in the region.